Multifaceted aseptic protocol decreases surgical site infections following hip arthroplasty. Issue 2 (March 2018) - Harold, Ryan E.; Butler, Bennet A.; Lamplot, Joseph; Luu, Hue H.; Lawton, Cort D.; Manning, David
Introduction: We investigate the effectiveness of a comprehensive aseptic protocol in reducing surgical site infection (SSI) after hip arthroplasty in a single medical centre with a high prevalence of methicillin-resistant Staphylococcus aureus (MRSA). Methods: A prospectively collected database of all patients undergoing hip arthroplasty in a single centre between 2005 and 2011 was reviewed for SSI using Centers for Disease Control (CDC) criteria and AAOS guidelines. All patients were administered an aseptic protocol consisting of: preoperative 2% mupirocin nasal ointment and 0.4% chlorhexidine surgical-site wipes; modified instrument care; perioperative prophylactic vancomycin and cefazolin; and surgical-site skin preparation with chlorhexidine, alcohol and iodophor. We compare our protocol hip arthroplasty SSI rate to our institutional historical control and to contemporary literature. Results: Among 774 patients, 69% were ASA>2, 45% had BMI≥30 and 10.3% had rheumatoid arthritis. We found an overall 0.39% infection rate; significantly lower than our institutional historical control (0.39% vs. 2.60%, p<0.001, OR 0.15, NNT 200) and significantly lower than 6 published reports (p<0.001-0.022, OR 0.16-0.22). Compared to these cohorts, significantly more of our patients were ASA>2, had BMI≥30 or had rheumatoid arthritis. Patients with 3 or more identifiable risk factors were at an increased risk of SSI compared to those with 2 or fewer risk factors. Conclusions: Our aseptic protocol decreases SSI in a high-risk population undergoing hip arthroplasty in a medical centre and community with a high prevalence of MRSA.